The changing role of the Irish local government manager - Asquith, Andy; O'Halpin, Eunan (Walter de Gruyter, 1998)
This article examines the degree and nature of change in the roles of Irish local government managers over the last decade. The research upon which the article is based has been conducted as a component part of the UDITE Leadership Study. The UDITE Leadership Study is a major collaborative research project being undertaking on behalf of Union des Dirigeants Territoriaux de l'Europe (UDITE or Association of the European Local Government Chief Executives). This trans-European study is concerned with the changing roles played by local government managers/chief executives. The specific aims of the study are to explore the rise in managerialism (Pollitt, 1993) in European local government, and to assess the impact this has upon the changing leadership and managerial roles of local government managers, and on relationships between managers and elected representatives (in Ireland, councillors).